Macroeconomic Drivers of GDP per Capita Growth in Five Middle-Income ASEAN Countries - Choirunnisa, Nur Haniifa; Yusfi, Reikha Habibah (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study aims to analyze the influence of Gross Fixed Capital Formation, exports of goods and services, remittances, and inflation on Gross Domestic Product per capita in five middle-income ASEAN countries: Malaysia, Thailand, Indonesia, Vietnam, and the Philippines.Method: A quantitative approach is employed utilizing panel data regression analysis. The Fixed Effects Model (FEM) is applied, selected based on the outcomes of the Chow and Hausman tests. Secondary data are sourced from the World Bank, encompassing the period from 2000 to 2023, yielding a total of 120 observations (5 countries over 24 years).Result: The empirical findings indicate that Gross Fixed Capital Formation, exports of goods and services, and remittances each have a positive and statistically significant effect on GDP per capita. Conversely, inflation exhibits a significantly negative impact. These results underscore that investments, export activities, and remittance inflows contribute to economic growth, whereas inflation diminishes purchasing power and may impede progress beyond the middle-income trap.Practical Implications for Economic Growth and Development: Governments in middle-income ASEAN countries should prioritize physical investment, enhance export markets, direct remittances toward human capital development, and implement effective monetary policies to regulate inflation and foster sustainable growth.Originality/Value: This study provides a novel contribution by integrating four key macroeconomic variables into a cohesive cross-country panel framework focused on ASEAN. It offers updated empirical evidence to enhance the understanding of the dynamics of GDP per capita and its correlation with the risks associated with the middle-income trap in the region.